2022
DOI: 10.1093/oncolo/oyab020
|View full text |Cite
|
Sign up to set email alerts
|

Use of Single-Item Self-Rated Health Measure to Identify Frailty and Geriatric Assessment-Identified Impairments Among Older Adults with Cancer

Abstract: Background Poor self-rated health (SRH) is a known predictor of frailty and mortality in the general population; however, its role among older adults with cancer is unknown. We evaluated the role of SRH as a potential screening tool to identify frailty and geriatric assessment (GA)-identified impairments. Materials and Methods Adults ≥60 years diagnosed with cancer in the UAB Cancer & Aging Resilience Evaluation (CARE) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…The reason may be that the strong sedative effect causes a lack of subjective motivation and energy, which leads to laziness, limited activity, and frailty ( 39 ). Self-reported health is a widely used health criterion to predict and identify frailty ( 40 , 41 ). The concept of frailty self-perception can explain the relationship between self-rated health status and frailty.…”
Section: Discussionmentioning
confidence: 99%
“…The reason may be that the strong sedative effect causes a lack of subjective motivation and energy, which leads to laziness, limited activity, and frailty ( 39 ). Self-reported health is a widely used health criterion to predict and identify frailty ( 40 , 41 ). The concept of frailty self-perception can explain the relationship between self-rated health status and frailty.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were required to have nonmissing data for at least 30 items in order to compute a valid frailty score and were categorized as robust (0–0.2), prefrail (0.2–0.35), and frail (>0.35), as previously described 24 . Our team has previously shown that the CARE frailty index predicts functional decline, severe chemotherapy toxicities, and survival among older adults; 25 similarly constructed frailty indices have shown comparable results 12–15,26 . See Table S1 for a full list of the CARE frailty index items.…”
Section: Methodsmentioning
confidence: 99%
“…Fifteen studies were speci cally conducted in the medical oncology setting, 19,20,23,24,[26][27][28][29][33][34][35]38,43,51,54 eight studies in surgical oncology, 41,42,45,49,52,53,55,56 and the remainder were either mixed or not speci ed. 17,18,22,25,[30][31][32]36,37,39,40,44,[46][47][48]50,57,58 Fourteen studies included a range of cancers and the rest focused on individual cancer types.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…17,18,22,25,[30][31][32]36,37,39,40,44,[46][47][48]50,57,58 Fourteen studies included a range of cancers and the rest focused on individual cancer types. 20,[22][23][24][25]30,32,36,39,40,44,46,47,50,57,58 There were 10 studies of breast cancer, [17][18][19][26][27][28][29]33,37,56 of which six studies were different secondary analyses of the same prospective clinical trial. 19,26,27,33 Similarly, two 34,51 of the ve lung cancer studies utilised the same retrospective database, 34,35,…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation